Prokaryotic communities in multidimensional bottom-pit-mud from old and young pits used for the production of Chinese Strong-Flavor Baijiu. (15th May 2020) - Zhang, Huimin; Meng, Yajing; Wang, Yanli; Zhou, Qingwu; Li, Anjun; Liu, Guoying; Li, Jingxin; Xing, Xinhui
Highlights: The bottom-pit-mud (BPM) prokaryotic communities differentiate in multidimensional. The old BPM differentiate vertically, 0–1 cm is abundant in Caproiciproducens . The young BPM differentiate between quarter/center and deep corner. A comprehensive process for BPM prokaryotic and physicochemical aging is proposed. Abstract: The pit mud (PM) prokaryotic communities with obvious difference between old and young PM is essential for solid-fermentation of Chinese Strong-Flavor Baijiu. The bottom-PM (BPM) is considered more important. In this study, the multidimensional prokaryotic communities of old and young BPMs were investigated. The old BPM presented stratified difference within the depth of 0–7 cm, especially, the surface 0–1 cm was characteristic of dominant Caproiciproducens (34.79%). The young BPM showed significant difference between quarter/center and deep corner (1–7 cm), the former were characteristic of abundant Lactobacillus (12.80%–42.72%), while the deep corner was distinctive of dominant Caproiciproducens (17.85%–64.45%). The lactic acid, pH and soluble Ca 2+ were considered as the 3 most significant environmental factors through redundancy analysis (RDA). This study may help illuminate the BPM aging process, and allow the future artificial regulation of young BPM.